THE IMPORTANCE OF REFORMS IN THE FIELD OF JUDICIAL LAW IN THE STRATEGY “UZBEKISTAN – 2030” - Zokirov Sherzod (Web of Journals Publishing, 2023)
This article discusses about the importance of reforms related to the judicial sphere in the newly adopted strategy “Uzbekistan – 2030”. The main ideas, goals and directions related to the judicial sphere in the strategy “Uzbekistan – 2030” are analyzed.
Keywords: Constitution, Strategy, goal, main directions, UN.